Microsoft Teams Gamification Strategy for Engaging Motivation and Building Fluency in English Language Learners - Rizky Eka Prasetya (Universitas Muhammadiyah Tangerang, 2025)
This study investigates the impact of gamification features within Microsoft Teams applications on language learning experiences. This study employs a mixed-methods approach to investigate the research questions comprehensively. The participants in this study will be 121 English Language Learners (ELLs) enrolled in virtual language classrooms. A diverse sample of ELLs from different proficiency levels and backgrounds will be recruited to ensure a comprehensive understanding of the impact of gamification. The findings of the Kolmogorov-Smirnov tests conducted on pre-tests and post-tests indicate notable changes in motivation levels following exposure to gamification. Specifically, the pre-test and post-test scores of ELLs in the experimental group (EG) exposed to gamification demonstrate a higher mean difference than those in the control group (CG) without gamification elements. The Gamification Group demonstrated a significantly higher mean score in Microsoft Team Gamification Learning Strategies, indicating a more robust engagement with gamified language learning activities within the Teams platform. The thematic analysis of participant responses highlights the specific gamification elements that play a crucial role in enhancing language fluency. The particular Microsoft Teams application that is most influential in gamification for language learning is the application. The survey findings reveal strong agreement among participants regarding the positive impact of various gamification elements integrated into the Microsoft Teams gamification application. The findings underscore the potential of gamification in transforming language learning experiences and promoting active engagement within virtual language classrooms. By leveraging gamification strategies effectively, educators and instructional designers can create immersive and interactive learning environments that facilitate language acquisition and proficiency development among English LanguageÂ